ANALISIS PENGARUH BEBAN PAJAK, PROFITABILITAS, MEKANISME BONUS DAN EXCHANGE RATE TERHADAP TRANSFER PRICING PADA PERUSAHAAN SEKTOR BARANG BAKU DI BURSA EFEK INDONESIA - Denny, Denny; Haryadi, Dedi; Suanti, Suanti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
Transfer pricing is the practice used by multinational companies to determine prices in transactions between subsidiaries, divisions, or related entities in different countries. The primary purpose of transfer pricing is to determine fair and reasonable prices for goods, services, or intellectual property rights traded between different entities that are within one company but operate in different countries or tax jurisdictions. The purpose of this study is to identify the effect of tax burden, profitability, bonus mechanism and exchange rate on transfer pricing in raw goods sector companies listed on the Indonesia Stock Exchange. The analytical tool used in the study was to use the Statistical Product and Service Solution (SPSS) program version 26. The sampling method is purposive sampling where there are 160 observational data. The results showed that tax burden, profitability, bonus mechanism and exchange rate have a positive effect on transfer pricing